On totally contact umbilical submanifolds of a manifold with a sasakian 3-structure - C ílin, Constantin (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES-VE X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Véase resumen en archivo PDF